THE POSITION OF DAUGHTERS IN THE DISTRIBUTION OF INHERITANCE IN BATAK TOBA AND MINANGKABAU COMMUNITIES - Yessy Octavianna; Nenni Triana Sinaga (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
The purpose of this research is to know how the distribution of inheritance and the position of daughters in the distribution of inheritance in Batak Toba and Minangkabau communities. This research uses descriptive qualitative research method. The data of this research consist of primary data and secondary data. Primary data was taken from the interview result of researcher with informant from both tribes, while secondary data was taken through literature study from journals, books and literature related to the problem under study. The results of this research show that in the Batak Toba community, daughters do not get a share of inheritance. The kinship system of the Batak Toba community embraces the patrilineal system, in which the lineage is withdrawn from the father's clan so that the inheritance belongs only to the sons. All heritages can only be passed on to the sons. But daughters can get the inheritance that is called holong ate. Holong ate is only given to married girls. The wealth gift is considered a gift of a father to his daughter. While in the Minangkabau community that embraces the matrilineal family system, where the familial system is withdrawn from the mother line, the heritage treasures are only given to daughters. Sons do not have high treasures and the low treasure (search treasure) is given to children and wives.